25th Anniversary of Traditional and Natural Medicine in the Medical School "Raúl Dorticós Torrado" - Silvia María Celorio Serrano; Omar Morejón Barroso (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
-